2014
DOI: 10.15190/d.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

New Frontiers for the NFIL3 bZIP Transcription Factor in Cancer, Metabolism and Beyond

Abstract: The bZIP transcription factor NFIL3 (Nuclear factor Interleukin 3 regulated, also known as E4 binding protein 4, E4BP4) regulates diverse biological processes from circadian rhythm to cellular viability. Recently, a host of novel roles have been identified for NFIL3 in immunological signal transduction, cancer, aging and metabolism. Elucidating the signaling pathways that are impacted by NFIL3 and the regulatory mechanisms that it targets, inhibits or activates will be critical for developing a clearer picture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 78 publications
1
20
1
Order By: Relevance
“…The b-ZIP transcription factor, E4BP4, is abundantly expressed in immune cells, liver, and bone (35). We previously reported an elevated level of E4bp4 mRNA in the refed liver and its induction by insulin in hepatocytes (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The b-ZIP transcription factor, E4BP4, is abundantly expressed in immune cells, liver, and bone (35). We previously reported an elevated level of E4bp4 mRNA in the refed liver and its induction by insulin in hepatocytes (39).…”
Section: Discussionmentioning
confidence: 99%
“…The b-ZIP transcription repressor, E4-binding protein 4 (E4BP4), also called nuclear factor interleukin-3-regulated (NFIL3), plays an essential role in innate immunity (34,35). The mRNA oscillations of E4bp4 were detected in the suprachiasmatic nuclei, liver, adipose tissues, aorta, skeletal muscles, and adrenal glands (36,37).…”
Section: Generation Of Adenovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a b-ZIP transcription factor, E4BP4 is ubiquitously expressed in various tissues, particularly abundant in the liver, spleen, and adipose tissue. 22 Although E4BP4 is well-known for its critical role in NK cell development and lymphocytes 23,24 and has been recently implicated in hepatic gluconeogenesis and the regulation of body composition, 25,26 the involvement of E4BP4 in lipid metabolism remains largely unexplored. We previously reported that potent induction of E4BP4 by insulin contributes to the postprandial de novo lipogenesis in an SREBP-1c-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3E, F shows the top 5 transcription factors predicted to regulate genes within 5 kb of the transcription start site of up-regulated or down-regulated genes, respectively. Ctcf is involved in gene regulation of multiple cell types, whereas the transcription factor families of IRF, Nfil3, and Stat are enriched in inflammatory cells and related processes (27)(28)(29). Gabpa, aka NRF2, is involved in metabolism and survival (30).…”
Section: Sca-1 + Reconstitution Induces Dramatic Transcriptional Chanmentioning
confidence: 99%